Computer Algebra System and Ancient Indian Mathematics - Das, Uttam; Mehera, Chitralekha (International Journal of Computer Sciences and Engineering, 2025)
Computer science and Mathematical science go hand in hand in the current ongoing scenario. Arithmetic operations are the base of any digital circuit. The present era of digitization focuses on the increment in the speed of digital circuits as well as reduction in size and power consumption; thus increasing the efficiency of the entire digital circuit. The contribution of Ancient Indian Mathematicians in this regard is of significant importance. They provided unique techniques of speedy computation in the form of Sutras. These sutras are actually algorithms. This paper describes some of the salient features and Sutras on Fundamental Arithmetic Operations of the Ancient Indian Mathematics